Effect on mechanical and thermodynamic properties of Al-10Si-0.8Fe alloys with Al-Ti-C and Ce compound additions. (4th May 2022) - Tang, Peng; Lai, Jinsheng; Lin, Yuying
ABSTRACT: In this work, OM, SEM/EDS, XRD, DSC, and tensile test were used to study the effect on mechanical and thermodynamic properties of Al-10Si-0.8Fe alloys with Al-Ti-C (0.5 wt.%) and xCe (viz. 0.2, 0.4, 0.6 and 0.8 wt.%) compound addition. After adding compound additives to Al-10Si-0.8Fe, the average size of SDAS decreased and the mechanical properties increased. When Ce is 0.6 wt.%, The smallest SDAS size and the best mechanical properties were obtained, then the melting range and enthalpy of melting also reached the minimum. Al-Ti-C can form submicron TiC in the melt, which refines the grains, and adding Ce can form Ce5 Si3 to round the needle-like Fe-rich phase and reduce the adverse effect, the composite additions of them synergistically improve the properties of Al-10Si-0.8Fe alloy. But excessive Ce could aggregate Ti and Fe-rich phases, then coarse impurity particles could form in the melt, leading to modification failure and performance deterioration.